Land deformation monitoring and spatiotemporal evolution characteristics analysis of coal mine goaf in Jilin Province based on time series InSAR - Yibin ZHANG; Jinhong SONG; Yuwei XU; Siyu XU (Shuiwen dizhi gongcheng dizhi)
A large number of goafs left by coal mining in Jilin Province has caused serious surface subsidence, which has brought serious hidden dangers to the goafs land and the transformation and upgrading of economic structure. To fill the gap in the research on surface deformation of coal mine goaf in Jilin Province, the SBAS-InSAR technology was used to quantitatively analyze the surface deformation from 2017 to 2021 (Sentinel-1B orbital drop data, 957 scenes). The reliability of the monitoring results of InSAR technology was verified through accuracy assessment and field investigation. The development trend of surface deformation in coal mine goaf in Jilin Province was analyzed and discussed. The results show that significant surface subsidence occurred in 11 goaf areas such as Yingcheng, Yangcaogou, and Shuangyang. The surface landfilling uplift was caused by subsidence control in the goafs of Meihekou, Wanbao, and Hunchun Fuqiang. From 2017 to 2021, the total subsidence area of coal goaf in Jilin Province is 71.47 km2, with the maximum subsidence rate of 243.16 mm/a and the maximum cumulative subsidence amount of 1104.3 mm. During the monitoring period, the overall surface subsidence of the coal goaf in Jilin Province is relatively slow. The nine goafs with more than heavy subsidence, such as Yangcaogou, Hunjiang, and Jiangyuan, have serious subsidence in the central areas, among which the Yangcaogou goaf subsidence is the most serious. The surface subsidence of coal mine goaf in Jilin Province is mainly caused by large-scale mining of underground coal resources, and the “activation” of shallow goaf is an important factor. The formation lithology and engineering geological characteristics of soft rocks also play a certain role in promoting it.